Boosting the Productivity of Bread Wheat (Triticum aestivum L.) Varieties through Optimal Seed Rates and Appropriate Systems for Irrigation Production System of Northwestern Ethiopia - Zelalem Yadelew (Turkish Journal of Agriculture: Food Science and Technology)
The availability of high-yielding varieties adapted to diverse agro-ecologies and production systems, preferred by farmers and consumers, is the key factor limiting productivity. Farmers access seeds of different quality levels from various seed systems. Studies on seed systems and rates in relation to yield and yield traits of bread wheat varieties under irrigation are limited. Therefore, an experiment was conducted in 2021 in Northwestern Ethiopia to improve the productivity of bread wheat (Triticum aestivum L.) varieties through suitable seed rates and systems under irrigation. The experiment was conducted using a randomized complete block design in a factorial arrangement of two varieties (Kakaba and Ogolcho), three seed systems (formal, intermediate and informal), and three seed rates (125, 150, and 175 kg ha-1) in three replications. SAS software was used for analysis. The results showed that the seed system and variety interaction had a significant effect (P < 0.05) on productive tiller numbers, days to 50% heading, kernel numbers per spike, and plant height. Additionally, the productive tiller numbers and days to 50% heading were significantly (P < 0.05) influenced by the interaction of variety with seed rate. However, the main effects of seed system, seed rate, and variety alone had a significant (P < 0.05) impact on physiological maturity, 1000-seed weight, kernel length, grain yield, biomass yield, and harvest index. The highest grain yields were obtained from the following main factors: seed system (intermediate (4.52 t ha-1); seed rate (150 kg ha-1 (4.71 t ha-1)); and variety (Kakaba (4.47 t ha-1)), which exceeded the average yield in irrigation (4.4 t ha-1). It is necessary to conduct experiments involving a greater number of seed rates and varieties over multiple cropping seasons and locations and sowing dates to strengthen the results.